Alqur’an dan Sains (Suatu Sudut Pandang Terhadap Legalitas Penafsiran Sains Atas Al-Qur'an) - Husnel Anwar Matondang; Sabriandi Erdian (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2013)
As a complete guidance, Qur’an needs to be relied on responding any important event surrounding the human itself both spritually and timely. Fundamental scientists have a legitimation to interpret Qur’an from many perspectives or various interpretations, for example: history, language, law, words/ sayings, correlation, etc. In addition, the science can also be legitimated to analyze the meanings in the Qur’an verses. The contextual interpretation in interpretating the : history, language, law, words/ sayings, correlation will not set free of the Quran verse itself. It is because the Qur’an itself is an absolut truth from Allah.Meanwhile, interpretation is a truth from human in which the truth itself can be right or wrong. The similiar thing also happens inscience interpretation. It is an eloquent decisions though it has the mistakes.